Fluency plus : managing fluency disorders in individuals with multiple diagnoses - Scott, Kathleen Scaler, 1969- (SLACK Incorporated, 2018)
"Fluency disorders such as stuttering, cluttering, and atypical disfluency are often accompanied by concomitant speech and language disorders, as well as other disorders impacting and interacting with fluency. Despite this common presentation, there is little training for speech-language pathologists to confidently treat fluency disorders and concomitant disorders together. Fluency Plus: Managing Fluency Disorders in Individuals with Multiple Diagnoses fills this much-needed gap, providing a strong research base along with practical strategies and treatment activities to guide speech-language pathologists in managing clients with fluency and concomitant disorders. Dr. Kathleen Scaler Scott brings her years of clinical experience and her research in the area of cluttering and atypical disfluencies to bear in Fluency Plus, designing it to act as both a textbook for students and a practical guide for the clinician. The comprehensive review of current definitions of fluency disorders and the evidence base for treatments will be of great help to students, while clinicians will appreciate the specific guidelines, strategies, and activities for managing fluency in concomitant disorders. After reviewing general principles and covering how executive functions relate to the management of these multiple concerns, the text addresses seven concomitant disorder areas the speech-language pathologist may encounter in practice. For each disorder category, an overview of potential fluency problems is provided, myths regarding treatment of fluency disorders in each population are debunked, and effective treatment activities are recommended"--Provided by publisher.